On Maximizing the Channel Gain for an IRS-aided Indoor VLC System with Blockages - Kumari, Pooja; Zaid, Md; Singh, Anand; Bohara, Vivek Ashok; Srivastava, Anand (International Symposium on Advanced Networks and Telecommunication Systems, 2023)
Visible light communication (VLC) is a promising complementary technology for the existing radio frequency (RF) communication. However, one of the drawbacks of the VLC system is the requirement of a line of sight (LoS) link to facilitate a high throughput communication between the transmitter and the receiver. Intelligent reflecting surfaces (IRS) have recently been proposed to solve this problem in the indoor VLC systems. This paper presents an optimization framework to maximize the IRS channel gain and determine the corresponding optimum pair of rotation angles of IRS elements in the presence of blockages for an indoor VLC system. Furthermore, the proposed framework compares two IRS allotment strategies among the users and examines the impact of IRS rotation angles on the received power. In the first approach, we use a regular horizontal allotment strategy. In the second approach, a channel-gain-based algorithm is developed to maximize the channel gain among the users. Simulation results show that the proposed channel-gain-based algorithm outperforms the horizontal allotment of IRS elements for the varying user locations in the presence of blockages.